Physical activity and brain health in patients with atrial fibrillation. (28th December 2022) - Herber, Elena; Aeschbacher, Stefanie; Coslovsky, Michael; Schwendinger, Fabian; Hennings, Elisa; Gasser, Andreas; Di Valentino, Marcello; Rigamonti, Elia; Reichlin, Tobias; Rodondi, Nicolas; Netzer, Seraina; Beer, Juerg H.; et al.
Abstract: Background and purpose: Vascular brain lesions, such as ischemic infarcts, are common among patients with atrial fibrillation (AF) and are associated with impaired cognitive function. The role of physical activity (PA) in the prevalence of brain lesions and cognition in AF has not been investigated. Methods: Patients from the multicenter Swiss‐AF cohort study were included in this cross‐sectional analysis. We assessed regular exercise (RE; at least once weekly) and minutes of weekly PA using a validated questionnaire. We studied associations with ischemic infarcts, white matter hyperintensities, cerebral microbleeds, and brain volume on brain magnetic resonance imaging and with global cognition measured with a cognitive construct (CoCo) score. Results: Among 1490 participants (mean age = 72 ± 9 years), 730 (49%) engaged in RE. In adjusted regression analyses, RE was associated with a lower prevalence of ischemic infarcts (odds ratio [OR] = 0.78, 95% confidence interval [CI] = 0.63–0.98, p  = 0.03) and of moderate to severe white matter hyperintensities (OR = 0.78, 95% CI = 0.62–0.99, p  = 0.04), higher brain volume ( β ‐coefficient = 10.73, 95% CI = 2.37–19.09, p  = 0.01), and higher CoCo score ( β ‐coefficient = 0.08, 95% CI = 0.03–0.12, p  < 0.001). Increasing weekly PA was associated with higher brain volume ( β ‐coefficient = 1.40, 95% CI = 0.65–2.15, p  < 0.001). Conclusions: In AF patients, RE was associated with a lower prevalence of ischemic infarcts and of moderate to severe white matter disease, with larger brain volume, and with better cognitive performance. Prospective studies are needed to investigate whether these associations are causal. Until then, our findings suggest that patients with AF should be encouraged to remain physically active. Abstract : The importance of physical activity in the prevalence of brain lesions, brain volume, and cognitive function among patients with atrial fibrillation is unknown. Participants from the multicenter Swiss‐AF cohort study were included in this cross‐sectional analysis. In atrial fibrillation patients, regular exercise was associated with a lower prevalence of ischemic infarcts and of moderate to severe white matter disease, with larger brain volume, and with better cognitive performance.